DNA Methylation and SNP-Mediated HLA-F Expression and Clinical Significance in Chronic Hepatitis B. (2021) - Hu, Xue-Qing; Zhou, Yuan; Chen, Jian; Zhao, Yu; Lu, Yi-Yu; Su, Shi-Bing
No abstract available